Effect of ambient PM2.5 on healthcare utilisation for acute respiratory illness, Melbourne, Victoria, Australia, 2014-2019. (1st February 2023) - Bailie, Christopher R.; Ghosh, Jo Kay C.; Kirk, Martyn D.; Sullivan, Sheena G.
ABSTRACT: Ambient particulate matter (PM2.5 ) is an important component of natural and human-generated air pollution and a major contributor to the global burden of disease. Short-term effects of PM2.5 exposure on respiratory illness have been described but most evidence arises from high pollution settings. We used case-crossover methods to estimate effects of outdoor PM2.5 levels on emergency department (ED) presentations and hospital admissions for a range of acute respiratory illnesses and age groups in Melbourne, Australia from 2014–2019, with and without adjustment for other pollutants and weather conditions, using daily and one-week averaged lags. We estimated incidence rate ratios for a 10 μg/m 3 increase in 7-day average ambient PM2.5 of 1.043 (95% confidence interval (CI): 1.000–1.089) on ED presentation and 1.013 (95% CI: 0.971–1.056) on hospital admissions for acute respiratory illnesses for patients of any age. We observed distinct temporal patterns in daily lag effect by disease. The largest effects on acute lower respiratory tract infection and asthma were observed in children. Ambient PM2.5 levels rarely exceeded standards in place at the time. Although uncertainty around most point estimates was relatively wide, these findings are most compatible with adverse health effects of ambient PM2.5 at levels below currently established Australian national standards. Implications : Understanding the health impacts of air pollution is important for setting air quality targets, as well as for informing robust health system planning. Adverse effects of exposure to outdoor fine particulate matter on human respiratory health have been consistently described. However, most studies have been done in higher-pollution settings. Further, many studies have assessed health effects in broad categories such as all-cause respiratory mortality or hospitalization, and thus lack the granularity to inform detailed health service planning. Our study aimed to estimate effects of outdoor fine particulate matter on emergency department (ED) presentations and hospital admissions for a range of acute respiratory illnesses and age groups in Melbourne, Australia, a city with relatively good air quality by international comparison. Our study estimated consistent effects on both ED presentations and hospital admissions compatible with distinct patterns of adverse health effects at levels at or below established Australian national (and many international) standards. These results will help to inform both air quality policy and public health policy in similar settings.